Antecedents of Customer Satisfaction in Increasing Muslim Customer Loyalty in Halal Restaurants - Mamuaya, Nova Ch.; Pandowo, Aditya (EQUILIBRIUM, 2024)
This research integrates product quality and perceived price with halal labeling to increase insight into purchasing behavior in consuming halal products. This study aims to explore the role of Muslim consumer satisfaction as well as its antecedents and consequences. The sample in this study was 100 Muslim respondents who visited fast food restaurants at least twice in the last month and were 18-25 years old. Data collection was carried out using a questionnaire survey around the city of Manado. The analysis technique used is the Structural Equation Model with Partial Least Square. The results showed that halal labeling, perceived price, product quality, and satisfaction had a significant effect on loyalty directly. In contrast, the indirect effect shows that perceived price does not significantly influence loyalty through satisfaction. The results of this study prove that the relationship between young Muslim consumers' satisfaction with the halal label and product quality can strengthen their loyalty. Therefore, companies must continue to maintain customer satisfaction. This research has certain limitations, namely that it focuses only on fast-food restaurants in Manado City and has only explored the mediating role of customer satisfaction. Practitioners and academics need to do further research in the future, especially in the context of halal products.